Neofidia Strother, a new name for Fidia Baly, 1863 and redescription of Fidia kanaraensis (Jacoby, 1895) with a new host record and notes on natural history (Coleoptera, Chrysomelidae, Eumolpinae) - Kumari, S. Amritha; Moseyko, A. G.; Strother, M. S.; Prathapan, K. D. (European Journal of Taxonomy, 2020)
Neofidia Strother nom. nov., is proposed as the replacement name for Fidia Baly, 1863, a junior homonym of Fidia Motschulsky, 1861 (not 1860, Griffin 1936). A list of the included species of Neofidia Strother nom. nov. and Fidia Motschulsky, 1861 is provided for clarity. Fidia medvedevi nom. nov. is the new replacement name proposed for Lypesthes vietnamicus Medvedev, 2015. Fidia kanaraensis (Jacoby, 1895) is redescribed and habitus, male and female genitalia are figured. Cashew (Anacardium occidentale L.) is reported as a new host of F. kanaraensis and partial information on the life history is provided. Eggs are laid singly on the surface of soil, and are covered with excreta and soil. Larvae tunnel into the tender roots. Adults are nocturnal and feed on tender leaves.